The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1111/j.1463-6409.1988.tb00097.x
|View full text |Cite
|
Sign up to set email alerts
|

The microtopography and papillar arrangement on adult Gorgoderina vitelliloba (Olsson) (Digenea, Gorgoderidae) from amphibians in relation to fish gorgoderids

Abstract: Specimens of Gorgoderina vitelliloba recovered from Rana temporaria and R. pipiens purchased in Eire are described using SEM. The microtopography is illustrated with particular emphasis on the type, number and arrangement of papillae. Significant differences in papillar arrangement were observed between the present specimens of G. vitelliloba from amphibians and that described earlier for the type species of Phyllodistomum from pike, Esox lucius, and Phyllodistomum from salmonids. The differences in papillae n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…1, 2, and 3). We used the existing terminology and classification of papillae established by Hoole and Mitchell (1981) and Bakke and Hoole (1988). Tegument of the rim of the oral sucker was smooth and had two types of papillae, domed papillae and rosette papillae (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 2, and 3). We used the existing terminology and classification of papillae established by Hoole and Mitchell (1981) and Bakke and Hoole (1988). Tegument of the rim of the oral sucker was smooth and had two types of papillae, domed papillae and rosette papillae (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Hong et al (1991) found domed papillae surrounding the oral and ventral suckers of recently excysted metacercariae of Heterophyopsis continua, but not on the dorsal surface. Bakke and Hoole (1988) found domed papillae on adult Gorgoderina vitelliloba, but again only surrounding the suckers. Transmission electron microscopy study is needed to understand the structure and function of domed, rosette, and ciliated papillae in Q. quinqueserialis.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of sensory papillae on surface of body, i.e. ciliated papillae (type II, sensu Hoole & Mitchell, 1981;Bakke & Hoole, 1988) and domeshaped papillae (Hoole & Mitchell, 1981;Bakke & Hoole, 1988). Ciliated papillae predominant and symmetrically distributed on ventral surface of lips (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements (length 9 width) in micrometres of the tegument spines and papillae were made from photomicrographs, and that of the remaining organs (mean followed by the range in parentheses) from mounted specimens using an ocular micrometer. The terminology and classification of digenean papillae follow Hoole & Mitchell (1981) and Bakke & Hoole (1988).…”
Section: Methodsmentioning
confidence: 99%
“…This character has often been used for their classification (Eduardo 1982(Eduardo , 1984Mata-Lopez and Leon-Regagnon 2006). Up to 4 types of papillae (button, ciliated, rosette, and domed papillae) were described by Hoole and Mitchell (1981), Bakke and Hoole (1988) and Mata-Lopez and Leon-Regagnon (2006) in various trematodes based on their shape. Eduardo (1982) emphasized the role of papillae in taxonomy and described up to 6 different types of papillae in paramphistomids (dome to conical non-ciliated papillae, dome to conical ciliated papillae, short and stumpy papillae covered by hair-like processes, long non-branching and non-ciliated papillae, long papillae with simple uniciliated branches, and long papillae with bulb-like multiciliated branches).…”
Section: Fine Structure Of Body Surfacementioning
confidence: 99%